SHARING SESSION EDUKASI MENGENAI PENYU DAN KEGIATAN PELEPASAN TUKIK DI KAWASAN KONSERVASI PENYU NIPAH, LOMBOK UTARA - Laily Fitriani Mulyani; Djonu, Asriati; Huriyatul Fitriyah Noor, Huriyatul Fitriyah Noor; Nandya Fitri Rachmawati, Nandya Fitri Rachmawati (Forum Komunikasi Dosen, 2024)
Educational Sharing Session Activities Regarding Turtles and Hatchling Release Activities held on November 9, 2024 in the Nipah turtle conservation area, North Lombok. This activity aims to increase public awareness and understanding of the importance of turtle conservation. This activity involves local communities, academics, and conservation area managers, with speakers from turtle conservation managers who provide education about the threats faced by turtles, such as illegal hunting, pollution, and habitat loss. In addition to the educational session, this activity also includes the release of hatchlings into the sea, providing an opportunity for participants to participate directly in turtle conservation. Interactive discussions that took place during the educational session allowed participants to ask questions and share knowledge about turtle conservation. The results of this activity show that the community is increasingly aware of the importance of their role in turtle conservation, and there is a commitment to be more involved in conservation efforts. Collaboration between the community, academics, and conservation managers is the main key to achieving the goal of sustainable turtle conservation. It is hoped that this activity can be a foundation for the development of further conservation programs that involve more parties and strengthen turtle conservation efforts in the future.